Framework for creating a qualified medical device development tool of autoinjectors - Machal, Marlon Luca (Frontiers in Medical Technology, 2023)
Objectives: Autoinjectors are pivotal for precise self-administration of medications across a wide range of medical conditions. Nevertheless, the absence of a dedicated Medical Device Development Tool (MDDT) for autoinjectors represents a gap that may result in variations in the quality and regulatory compliance of autoinjectors as components of combination products. This research aim is to utilise the recently introduced Primary Functions outlined in ISO 11608-1:2022 with the tittle “ Needle-based injection systems for medical use. Requirements and test methods. Part 1: Needle-based injection systems” to create a comprehensive MDDT framework tailored specifically for autoinjectors. Methods: To support the creation of the framework, the analysis of the FDA MDDTs that were already approved, FDA’s design controls regulations, FDA’s guidance related to autoinjectors, and the Primary functions outlined in ISO 11608-1:2022 were utilised. Results: The research identifies the Primary Functions in autoinjector to be Holding Force , Cap Removal Force, Activation Force, Extended Needle Length, Injection Time, Dose Accuracy, Needle Guard Lockout, and Holding Force. Leveraging these Primary Functions and the FDA's MDDT approach, the research aims to bridge the gap by proposing a structured framework for the development of a specific MDDT tailored to autoinjectors. Conclusion: This research, leveraging the newly established Primary Functions, presents a structured framework to develop a specific MDDT tailored for autoinjectors. This framework can be used to enhance the safety and effectiveness of medication delivery through a systematic approach and ultimately expediting the FDA approval of the autoinjector as part of a combination product.